Efektivitas atas Tata Kepemerintahan yang Baik dalam Penyelenggaraan Pengadaan Barang dan Jasa Pemerintah Kabupaten Karangasem - Sang Made Suartama; Cokorde Istri Dian Laksmi Dewi (Kajian Ilmiah Hukum dan Kenegaraan, 2022)
In the effort of good governance implementation an Indonesia, where the elimination corruption, collusion, and nepotism be priority agenda, Government publish to Presidential Regulation Number 16, 2018 about government procurement goods and service. Good Government procurement goods and service is a procurement system that include procedure to secure government institutions whose doing the goods and service procurement also can actualization the principles of good governance. Good procurement can push the efficiency and effectiveness of public expenses, guarantee fair competition. The scope of this thesis measured on the Effectiveness good governance principles in goods and service Procurement Regency of Karangasem. Purpose: Purpose of this thesis is to descriptions about Implementation good governance principles in goods and service Procurement Regency of Karangasem, what is the obstacle and also the solution take to solve the obstacle. Methodology: This thesis using a certain research method is empirical juridic approach, with the research specification including analytic descriptive. Type of data used is secondary data in form of narration and documentation, collecting by library studi and documentatary study, and then be normative analyzed. Results: Implementation good governance principles in goods and service Procurement Regency of Karangasem can’t be optimally, because lack of human resources quality, infrastructure and tools not support for application good government procurement. In the effort of implementation in good government procurement, Karangasem regency doing a few programs, that is marking up the quality of human resources, measuring goods and service procurement by performance standard, marking up infrastructure and tools of procurement.